2018
DOI: 10.11113/ijbes.v5.n3.307
|View full text |Cite
|
Sign up to set email alerts
|

Dual Formal and Informal Transport Modes towards Quasi-Seamless Transit in a Developing City

Abstract: Dual formal and informal transport modes have been complementing one another in Bandung City for more than four decades now. The issue appears due to inability of formal transport to provide adequate services to the citizens. However, this accompaniment has brought Bandung City to a quasi-seamless transportation process as both transport modes play their roles as a continuum. Amid insufficient public transportation system in Bandung City, the informal transport modes have properly paired their formal transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…from origin to destination. Based on a study by Permana et al, (2018) and Permana et al, (2015), the characteristics of formal and informal transport are shown in Table 3. In the case of formal, semi-formal, and informal public transports in Bangkok, the characteristics are almost the same as what is described in Table 3.…”
Section: Songteaw (Pickup)mentioning
confidence: 99%
“…from origin to destination. Based on a study by Permana et al, (2018) and Permana et al, (2015), the characteristics of formal and informal transport are shown in Table 3. In the case of formal, semi-formal, and informal public transports in Bangkok, the characteristics are almost the same as what is described in Table 3.…”
Section: Songteaw (Pickup)mentioning
confidence: 99%
“…Kumar et al (2021) argue that formal public transport, such as bus rapid transit (BRT), is not always a solution and there are different public transport markets in a city. Formal and informal transport modes can coexist under a well-integrated urban transport system (e.g., Permana et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The paper casts particular light on demand behavior in the market. The existing literature is relatively rich on the supply side, describing physical or operational characteristics of paratransit services (e.g., Shimazaki and Rahman, 1996;CDIA, 2011;Tichagwa, 2016;Permana et al 2018). However, the demand-side analysis has been carried out in a relatively limited number of studies thus far.…”
Section: Introductionmentioning
confidence: 99%